Ru-doped 3D porous Ni3N sphere as efficient Bi-functional electrocatalysts toward urea assisted water-splitting. (15th July 2022) - Liu, Yibing; Zheng, Debo; Zhao, Ying; Shen, Pei; Du, Yingxue; Xiao, Weiping; Du, Yunmei; Fu, Yunlei; Wu, Zexing; Wang, Lei
Abstract: Developing efficient, stable and ideal urea oxide (UOR) electrocatalyst is key to produce green hydrogen in an economical way. Herein, Ru doped three dimensional (3D) porous Ni3 N spheres, with tannic acid (TA) and urea as the carbon and nitrogen resources, is synthesized via hydrothermal and low-temperature treated process (Ru–Ni3 N@NC). The porous nanostructure of Ni3 N and the nickel foam provide abundant active sites and channel during catalytic process. Moreover, Ru doping and rich defects favor to boost the reaction kinetics by optimizing the adsorption/desorption or dissociation of intermediates and reactants. The above advantages enable Ru–Ni3 N@NC to have good bifunctional catalytic performance in alkaline media. Only 43 and 270 mV overpotentials are required for hydrogen evolution (HER) and oxygen evolution (OER) reactions to drive a current of 10 mA cm −2 . Moreover, it also showed good electrocatalytic performance in neutral and alkaline seawater electrolytes for HER with 134 mV to drive 10 mA cm −2 and 83 mV to drive 100 mA cm −2, respectively. Remarkably, the as-designed Ru–Ni3 N@NC also owns extraordinary catalytic activity and stability toward UOR. Moreover, using the synthesized Ru–Ni3 N@NC nanomaterial as the anode and cathode of urea assisted water decomposition, a small potential of 1.41 V was required to reach 10 mA cm −2 . It can also be powered by sustainable energy sources such as wind, solar and thermal energies. In order to make better use of the earth's abundant resources, this work provides a new way to develop multi-functional green electrocatalysts. Graphical abstract: Image 1 Highlights: The synthesized electrocatalyst exhibits porous specific sphere morphology to exposed abundant active sites. The prepared electrocatalyst presents excellent electrocatalytic performances toward HER, OER and UOR. Small overpotential is required to drive overall water-splitting under the urea assistance with remarkable stability. Sustainable energies are investigated to power the electrolyzer for hydrogen generation.